Detection of Astrovirus in Historical Cases of European Sporadic Bovine Encephalitis, Switzerland 1958–1976 - Selimovic-Hamza, Senija; Bouzalas, Ilias G.; Vandevelde, Marc; Oevermann, Anna; Seuberlich, Torsten (Frontiers in Veterinary Science, 2016)
European sporadic bovine encephalitis is a frequent diagnosis in neurologically diseased cattle, but its etiology remained unresolved. Using in situ hybridization, we have detected a recently discovered neurotropic bovine astrovirus in historical tissues in a high proportion of brain samples of affected cattle. Our results suggest that astroviruses were already involved in the pathogenesis of the disease several decades ago, but have gone undetected.